Área de Livre-Comércio das Américas: incentivos econômicos e políticos - Motta, Daniel Augusto (2002)
The purpose of this dissertation is to analyse the political economy of Free Trade Area of America based on a sequential non-cooperative Stackelberg political game between a large economy and a small economy, in which the political dispute of rival lobby groups define the unilateral stance of both governments in the first stage and the Stackelberg 'coalition-proof' equilibrium define the format of the free trade agreement in the second stage. Finally, I discuss a few modifications in the initial game structure in order to enhance the small economy's negotiation power.